Tungsten Catalyst Incorporating a Well‐Defined Tetracoordinated Aluminum Surface Ligand for Selective Metathesis of Propane, [(≡Si−O−Si≡)(≡Si−O−)2Al−O−W(≡CtBu) (H)2]. Issue 1 (21st December 2018) - Werghi, Baraa; Bendjeriou‐Sedjerari, Anissa; Jedidi, Abdesslem; Morlanes, Natalia; Abou‐Hamad, Edy; Bhatte, Kushal; Guan, Erjia; Ma, Tao; Aguilar‐Tapia, Antonio; Ould‐Chikh, Samy; Cavallo, Luigi; Gates, Bruce C.; et al.
Abstract: A well‐defined aluminium‐bound hydroxyl group on the surface of mesoporous SBA‐15, [(≡Si−O−Si≡) (≡Si−O)2 Al−OH], 3 was obtained by reacting di‐isopropyl aluminium hydride with SBA‐15 treated at 700 °C. The resulting surface [(≡Si−O−Si≡) (≡Si−O)2 Al (isobutyl) fragment undergoes β‐H elimination at 400 °C leading to [(≡Si−O−Si≡)(≡Si−O−)2 Al−O) Al−H]. Further oxidation of this Al‐hydride with N2 O leads to3 . This acidic support was used to create a well‐defined surface organo‐tungsten fragment [(≡Si−O−Si≡)(≡Si−O−)2 Al−O−W(≡C t Bu)(CH2 tBu)2 ] by reacting3 with W(≡C‐ t Bu)(CH2 ‐ t Bu)3 . A further reaction with hydrogen under mild conditions afforded the tungsten carbyne bis‐hydride [(≡Si−O−Si≡)(≡Si−O−)2 Al−O−W(H)2 (≡C‐ t Bu)]. The performance of each of the W‐supported catalysts was assessed for propane metathesis in a flow reactor at 150 °C. [(≡Si−O−Si≡)(≡Si−O−)2 Al−O−W(≡C t Bu)(H)2 ] was found to be a single‐site catalyst, giving the highest turnover number (TON=800) and the highest reported selectivity for butane (45 %) vs . ethane (32 %) known for oxide‐supported tungsten complex catalysts (with the supports being silica, silica‐alumina, and alumina). The results demonstrate that modification of the oxide ligands on silica via the creation of Al Lewis acid center as an anchoring site for organometallic complexes opens up new catalytic properties, markedly enhancing the catalytic performance of supported organo‐tungsten species. Abstract : Acid is good : Tetracoordinated aluminum hydroxide [(≡Si−O−Si≡)(≡Si−O)2 Al−OH] surface ligands were formed through [Al−H] oxidation using N2 O. These new sites were used as anchoring centers for the immobilization of a tungsten based complex W(≡C t Bu)(CH2 t Bu)3, leading to the generation of a monopodal well‐defined surface organo‐tungsten fragment [(≡Si−O−Si≡)(≡Si−O−)2 Al−O−W(≡C t Bu)(CH2 t Bu)2 ]. The activity of this new catalyst was evaluated in the propane metathesis reaction, where a TON of 800 was obtained, the highest value obtained for a SOMC monometallic catalyst.